HÁBITOS ALIMENTARES DE MULHERES NO PERÍODO DO CLIMATÉRIO - Sebotaio, Ana Luisa Concli; Unser, Juliana; Conte, Francieli Aline; Franz, Lígia Beatriz Bento (Salão do Conhecimento, 2018)
Projeto de Iniciação Científica